Effect of Sand Roasting on Physicochemical, Thermal, Functional, Antinutritional, and Sensory Properties of Sattu, a Nourishing form of Chickpea - Iqra Qureshi; Khalid Bashir; Shumaila Jan; Ayon Tarafdar; Mehvish Habib; Kulsum Jan (Journal of Food Quality)
Sattu is a traditional Indian food product made of chickpea with tremendous nutritional benefits. However, the processing of sattu has not been thoroughly explored which is an impediment to industrial applications involving the development of sattu-based products. These products carry immense benefits for consumers and for widespread popularity; it is essential that the roasting of sattu for further processing be investigated for improving the properties of sattu while reducing its antinutritional factors. In this study, the impact of sand roasting on the physicochemical, sensory, antinutritional, thermal, functional, and antioxidant properties on sattu was investigated. Chickpea grains were roasted in sand for different time periods (3–17 min) and temperature combinations (171–228°C). Results revealed that samples treated at 180°C for 15 min had maximum sensory score (3.99) followed by the samples treated at 200°C for 10 min and at 228°C for 10 min. Overall sattu roasted at 180°C for 15 min was found suitable for further application.